Do negative attitudes toward older adults vary by occupation? Focus on the stereotype content model - Kudo, Yasuyuki; Shimizu, Yuho; Karasawa, Kaori (Frontiers in Social Psychology, 2024)
Do negative attitudes toward older adults vary according to the occupation of the older adult? Addressing this question is crucial to foster continued employment opportunities for older individuals. To explore this, we conducted an online experiment with Japanese participants, examining how negative attitudes fluctuate when comparing non-older and older adults within specific occupations. This study applied the stereotype content model across 16 occupations and unveiled a three-cluster solution, indicating variations in stereotype mappings between non-older and older workers. Moreover, it was observed that the propensity for these differences varied across clusters. Notably, in occupations where the workers were perceived as more competent and warmer than the general older adults, stereotypes shifted more positively when participants were informed that the workers were older. Conversely, in occupations where workers were perceived as more competent and less warm, both competence and warmth shifted in a negative direction with the introduction of age information. In addition, respect—the degree to which the target person is esteemed and/or admired by others—was strongly associated with both competence and warmth. It is anticipated that the insights gleaned from this study can inform practical interventions aimed at mitigating negative attitudes toward older adults concerning employment.